Broad-scale sampling of primary freshwater fish populations reveals the role of intrinsic traits, inter-basin connectivity, drainage area and latitude on shaping contemporary patterns of genetic diversity - Santos, Carla Sousa (2016)
Background. Worldwide predictions suggest that up to 75% of the freshwater fish species occurring in rivers with reduced discharge could be extinct by 2070 due to the combined effect of climate change and water abstraction. The Mediterranean region is considered to be a hotspot of freshwater fish diversity but also one of the regions where the effects of climate change will be more severe. Iberian cyprinids are currently highly endangered, with over 68% of the species raising some level of conservation concern. Methods. During the FISHATLAS project, the Portuguese hydrographical network was extensively covered (all the 34 river basins and 47 sub-basins) in order to contribute with valuable data on the genetic diversity distribution patterns of native cyprinid species. A total of 188 populations belonging to 16 cyprinid species of Squalius, Luciobarbus, Achondrostoma, Iberochondrostoma, Anaecypris and Pseudochondrostoma were characterized, for a total of 3,678 cytochrome b gene sequences. Results. When the genetic diversity of these populations was mapped, it highlighted differences among populations from the same species and between species with identical distribution areas. Factors shaping the contemporary patterns of genetic diversity were explored and the results revealed the role of latitude, inter-basin connectivity, migratory behaviour, species maximum size, species range and other species intrinsic traits in determining the genetic diversity of sampled populations. Contrastingly, drainage area and hydrological regime (permanent vs. temporary) seem to have no significant effect on genetic diversity. Species intrinsic traits, maximum size attained, inter-basin connectivity and latitude explained over 30% of the haplotype diversity variance and, generally, the levels of diversity were significantly higher for smaller sized species, from connected and southerly river basins. Discussion. Targeting multiple co-distributed species of primary freshwater fish allowed us to assess the relative role of historical versus contemporary factors affecting genetic diversity. Since different patterns were detected for species with identical distribution areas we postulate that contemporary determinants of genetic diversity (species' intrinsic traits and landscape features) must have played a more significant role than historical factors. Implications for conservation in a context of climate change and highly disturbed habitats are detailed, namely the need to focus management and conservation actions on intraspecific genetic data and to frequently conduct combined genetic and demographic surveys.